(3Pjd faMI GdQjMGfIs - (3TeS GdOjf eMeO SYjO Hf eMeO Hf CMeO GdTgjQ H GHf GdSeGf GdOeTbj GdTGaYjs; (3GdeMHj , eMeO Gejf Hf aVd Gddg Hf eMH Gddg Hf eMeO GdeMHj GdMehj, eMH GdOjf , CHh HcQ,J (B1111 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B: (3efg Ydi eG SeYJ bOQkG abO HdZg Cfi GdJReJ Cf CVY Ydjg hVYkG LRdkG hdh LeY eG bQQJg s
(3BNQgG (B:s
(3eG fGMJ GdhQb ai GdQhGHi hdGM HGdCHQbjf HGQb Je s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B41 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B78s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B363 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B391 s
Keywords: (3GdJGQjNs